Review of the Third International Symposium on Georg Simmel - Medellín, Colombia. November 2011 - Cervantes Reyes, Haydeé; Botia Merchán, H.; Díaz Aldana, Gilberto; Mosquera Acevedo, Einer (Simmel Studies, 2016)
The University of Antioquia in Medellín, Colombia, was the scenario for holding what can be regarded now as a tradition in Latin America: an International Symposium on Georg Simmel. This review attempts to share the result of the third symposium outlining how simmelian categories were revisited and used as research keys for understanding the Latin American context. It is worth to mention that after the event not only the initiative of publishing the proceedings was achieved, but also the formalization of a Latin American simmelian studies network. This valuable experience of gathering around Simmel’s work will return to its initial point when the Fourth Symposium will be hold in Buenos Aires, Argentina, on November 2015.